Strategy of development for a banking system of Russia in the conditions of recession of economy - A. V. Rusavskaya (Путеводитель предпринимателя)
Recession of economy of many countries of the world demands development of the new strategy of development for all her spheres, including bank. The banking system of Russia can promote strengthening of small and medium business, joint financing together with the state of national projects, to the solution of problems of social protection of the population of Russia.